Analysis of aroma compounds derived from heated tsukudani seasoning liquid models containing rare sugars - Kimura, Isao; Izumori, Ken; Inazu, Tadao; Miyoshi, Miku; Tamura, Hirotoshi; Akimitsu, Kazuya (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
Three tsukudani seasoning liquid models of soy sauce and amino acid seasoning liquid mixed with rare sugar syrup (RSS, main rare sugars: d -allulose, d -sorbose, d -tagatose, d -allose), glucose-fructose liquid sugar (GF), and white sugar (WS) were heated in a headspace sampler to create a delicious aroma. The aroma components generated were then analyzed using HS-GC/MS. As a result of the Maillard reaction, brown color intensity measured at absorbance 420 nm in the RSS liquid was significantly higher than in the GF and WS liquids. Principal component analysis of the quantitative data of the aroma compounds revealed 1.1–4.5 times more furans such as furfural, furfuryl alcohol, 2,5-diethyl tetrahydrofuran, and 3-phenylfuran were released from RSS than from GF and WS, which contributed to the characteristic aroma components of the tsukudani seasoning liquid. These results suggest that the four main rare sugars in the RSS are involved in the aroma formation.